The Spatial Dimension of Early School Leaving in Campania Region: the Case of Scuola Viva Program - Sabatino, Pietro; Madonia, Emanuele; Ragozini, Giancarlo (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
Scuola Viva, a four-year program launched by Campania Region, over the course of its duration (2015/2019) has supported the implementation of learning, training and cultural experiences built thanks to the collaboration of schools, enterprises, citizens and other local actors (i.e., non-governmental organisations) in order to strengthen local learning communities. With respect to these premises, the objective of the contribution is to map and classify the regional territory on the basis of a synthetic index of “risk of dropout”, following other national examples and to verify how much Scuola Viva Program intercepted the young people most directly affected by the phenomena of early school leaving and educational poverty.